Elemental, structural and optical properties of nanocrystalline Zn1−xCuxSe films deposited by close spaced sublimation technique - Muhammad Arslan; Amir Habib; Muhammad Zakria; Arshad Mehmood; Ghulam Husnain (Journal of Science: Advanced Materials and Devices, 2017)
The elemental composition, film thickness and concentration depth profiles of as-deposited and annealed Zn1−xCuxSe films were studied by the Rutherford backscattering spectrometer (RBS) technique. The films were deposited on glass substrates by close spaced sublimation (CSS) technique. As-deposited films of about 250–300 nm thickness were then annealed in air at temperatures of 200 °C and 400 °C for 1 h. Structural characterization including crystal structure, crystal orientation, stacking fault energy (ҮSFE) and surface morphology were carried out by using X-ray diffraction (XRD) and atomic force microscopy (AFM). XRD studies revealed that the fabricated films are polycrystalline with a zinc-blende structure and a strong (111) texture plane. Surface roughness was observed to be enhanced with annealing temperature with a decrease in stacking fault energy (ҮSFE). Spectroscopic ellipsometry has been utilized for the estimation of band gap energy (Eg) and dielectric constant (ε1). Band gap energy of the film increased with increasing annealing temperature while the dielectric constant decreased.